2019
DOI: 10.1016/j.tele.2019.101250
|View full text |Cite
|
Sign up to set email alerts
|

Social media addiction: Applying the DEMATEL approach

Abstract: While there is a growing number of studies investigating the determinants of social media addiction, there is a lack of research on examining the importance of such predictors and their inter-correlations and interdependences from psychotherapists' and researchers' point of views. Hence, utilizing the "Decision Making Trial and Evaluation Laboratory (DEMATEL)" technique, the current study investigated the clinical importance of social media addiction from the perspective of researchers and psychotherapists. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 90 publications
2
86
1
Order By: Relevance
“…In terms of antecedents, studies have found that certain mental disorders such as anxiety, depression, and ADHD are all positively correlated to social media addiction [11]. They have also found that users with certain personality types, particularly users who are more extroverted, open to new experiences, agreeable, and neurotic, are at higher risk than others for developing an addiction to social media [8,12]. In terms of effects, studies have shown that social media addiction could lead to stress, relationship problems, and life dissatisfaction, amongst other complications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of antecedents, studies have found that certain mental disorders such as anxiety, depression, and ADHD are all positively correlated to social media addiction [11]. They have also found that users with certain personality types, particularly users who are more extroverted, open to new experiences, agreeable, and neurotic, are at higher risk than others for developing an addiction to social media [8,12]. In terms of effects, studies have shown that social media addiction could lead to stress, relationship problems, and life dissatisfaction, amongst other complications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the causes of social media addiction and the types of users who are more susceptible to addictive behavior. It has been observed that neuroticism (Leong et al 2019 ; Marengo et al 2020 ), depression, and loneliness (Dalvi-Esfahani et al 2019 ) are associated with social media addiction. Users who have more friends and followers (Longobardi et al 2020 ) and receive mostly positive feedback (Marengo et al 2020 ) on social networking sites are at a higher risk of getting addicted to social media.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these points, many researchers in the literature used the DEMATEL method in their analysis. As an example, Dalvi-Esfahani et al [56] evaluated social media addiction by applying DEMATEL methodology. Additionally, Abdel-Basset et al [57] focused on the selection of the best suppliers.…”
Section: B Literature On the Methodsologymentioning
confidence: 99%
“…This situation provides an opportunity to understand the causality relationship among the items. In the first step, expert opinions are collected by considering 5 different scales that are 0 (no influence), 1 (low influence), 2 (medium influence), 3 (high influence) and 4 (very high influence) [56]. By considering the average values of these evaluations, the direct relation matrix (A) is calculated as in the equation (34).…”
Section: Dematelmentioning
confidence: 99%